PENGUATAN IDENTITAS KEAGAMAAN DAN KEBANGSAAN DALAM MEMBANGUN DIALOG INTERRELIGIUS DI INDONESIA - Nikolas Novan Risbayana; Antonius Yuan Fimanda; Willfridus Demetrius Siga; Fransisxus Surya Tirta Lesmana; Vinsensius Hulu (Sapientia Humana: Jurnal Sosial Humaniora, 2022)
Today's religious identity is often understood and practiced in a negative context. Cases such as religion-based hate speech, identity politics, intolerance, and discrimination arise due to the wrong paradigm of strengthening religious identity. The purpose of this study is to offer another perspective on strengthening religious identity and nationality that puts forward global ethics as an alternative in strengthening religious identity through interreligious dialogue. This scientific article refers to research with a qualitative approach using the netnographic method which is a case study through digital data tracing. In addition, this research also raises the idea of ​​Hans Küng's global ethics. The results of this study are in the form of offers in developing interreligious dialogue in Indonesia, especially those related to the consistency of identity, culture, and Pancasila values ​​that put forward the principles of global ethics. Interreligious dialogue that needs to be worked out together is a dialogue that emphasizes human values.